Lessons Learned: Early Termination of a Randomized Trial of Calcineurin Inhibitor and Corticosteroid Avoidance Using Belatacept. Issue 10 (3rd July 2017) - Newell, K. A.; Mehta, A. K.; Larsen, C. P.; Stock, P. G.; Farris, A. B.; Mehta, S. G.; Ikle, D.; Armstrong, B.; Morrison, Y.; Bridges, N.; Robien, M.; Mannon, R. B.
Abstract : The intent of this National Institutes of Health–sponsored study was to compare a belatacept‐based immunosuppressive regimen with a maintenance regimen of tacrolimus and mycophenolate. Nineteen primary, Epstein–Barr virus–immune renal transplant recipients with a negative cross‐match were randomized to one of three groups. All patient groups received perioperative steroids and maintenance mycophenolate mofetil. Patients in groups 1 and 2 were induced with alemtuzumab and maintained on tacrolimus or belatacept, respectively. Patients in group 3 were induced with basiliximab, received 3 mo of tacrolimus, and maintained on belatacept. There was one death with a functioning allograft due to endocarditis (group 1). There were three graft losses due to vascular thrombosis (all group 2) and one graft loss due to glomerular disease (group 1). Biopsy‐proven acute cellular rejection was more frequent in the belatacept‐treated groups, with 10 treated episodes in seven participants compared with one episode in group 1; however, estimated GFR was similar between groups at week 52. There were no episodes of posttransplant lymphoproliferative disorder or opportunistic infections in any group. Protocol enrollment was halted prematurely because of a high rate of serious adverse events. Such negative outcomes pose challenges to clinical investigators, who ultimately must weigh the risks and benefits in randomized trials. Abstract : The authors report on a randomized controlled trial exploring a belatacept‐based immunosuppressive regimen that closed early because of unexpected graft losses attributed to technical issues, and demonstrate the important contributions of data safety monitoring board participants with investigators and sponsors.